A comparative study on the comprehensive strength of China's biomedical industry group under the background of supply side reform. Issue 5 (4th July 2018) - Yan, Shu-Rong; Tian, Man-Wen
Abstract: Background: in the context of deeply promoting supply-side structural reform in China, the bio-pharmaceutical industry of China is being boosted from three aspects of "adjusting structure, reducing costs and replenishing short-slab", and the comprehensive strength assessment of bio-pharmaceutical industry cluster has become the important issue focused by the academic circles. Methods: the comparative analysis was made for the comprehensive strength of China bio-pharmaceutical industry cluster on the basis of grey theory analysis by establishing the assessment indicator system and assessment model complying with the characteristics of Chinese bio-pharmaceutical industry. Results: the empirical study revealed that: the comprehensive strength of Chinese bio-pharmaceutical industry cluster in the Yangtze River Delta Region was higher than that of the bio-pharmaceutical industry cluster in the Pearl River Delta and the circum-Bohai-Sea, the comprehensive strength of the bio-pharmaceutical industry cluster in the Pearl River Delta was higher than that of the bio-pharmaceutical industry cluster in the circum-Bohai-Sea. Conclusions: the comprehensive strength of Chinese bio-pharmaceutical industry cluster has to improve further; Chinese bio-pharmaceutical industry cluster needs not only to grasp the opportunity of current supply-side reform to further optimize industrial structure, but also needs to focus on the supply-side elements to improve production efficiency of element and promote its transformation and upgrading.